Production of bacterial cellulose films by Gluconoacetobacter xylinus for lipase immobilization - Nguyen , Thuy Kim Anh; Huynh , Bao Ngan; Thai , Hoang Nguyen Vu; Tran , Thi Nhu Hao; Truong , Thi Thu; Vu , Tran Khanh Linh (Journal of Technical Education Science, 2021)
Bacterial cellulose (BC), a microbial polysaccharide, has chemically equivalent structure to plant cellulose with unbranched pellicle structure of only glucose monomers. Due to the unique nanostructure, BC has great potential in enzyme immobilization. In this study, the effects of different cultivation conditions including rotational speed, initial inoculum concentration and medium pH on the film-like cellulosic biomass formation of Gluconacetobacter xylinus JCM 9730 were examined. The resultant BC films were then studied for its feasibility in the immobilization of lipase, a widely used enzyme in biotechnological and industrial processes including food, pharmaceutical, chemical and paper industries. Results showed that increasing in rotational speed from 0 rpm to 200 rpm converted cellulose-producing cells to non-cellulose-producing ones, leading to a significant decline in BC film formation. The increase in initial inoculum size from 0.01 g/L to 0.1 g/L reduced sugar concentration and surface area of the medium, and therefore inhibiting the formation of film-like cellulosic biomass. In addition, the optimum pH range of Acetobacter species from 5.4 – 6.3 was found not optimal for BC film formation. The highest amount of film-like cellulosic biomass of 19.01 g/L was obtained under static condition (0 rpm) with initial cell concentration of 0.04 g/L and initial pH of 4.0. The BC film samples were then acetylated with acetic anhydride/iodine system to convert the hydroxyl groups to less hydrophilic acetyl groups and were used for lipase immobilization. Results showed that lipase immobilized on acetylated BC still maintained its lipid hydrolytic activity. It can be hence concluded that BC films produced by G. xylinus JCM 9730 were potential for lipase immobilization.